«Conformidad» in the Spanish Criminal Process: Analysis and Critical Judgment - Oliver Calderón, Guillermo Ramiro (2023)
«Conformidad» is a very old institution in the Spanish criminal procedure system, since it dates back to the 19th century. In recent decades it has experienced a notable increase in its application as a negotiated criminal justice mechanism, as a result of several modifications in the Law of Criminal Procedure that have sought to introduce more space for negotiation in said figure and encourage its use. However, as an unwanted effect, such modifications have made the already convoluted regulation of said institute more complex, which makes it difficult to understand its physiognomy. This paper examines the current state of «conformidad» in the Spanish Criminal Procedure Law. Its scope of application, its requirements, its content, its processing and its effects are reviewed in the ordinary procedure, in the abbreviated procedure and in the fast procedure. A critical analysis of «conformidad» is also carried out from considerations made by the Spanish doctrine based on the complex normative reality and the not always consistent practice of the system, highlighting the fact that said institution generates certain risks for the accused, for the victim and for society. The work ends with some brief conclusions.